2001
DOI: 10.3201/eid0704.010414
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of the West Nile Fever Outbreak, Israel, 2000

Abstract: West Nile (WN) virus is endemic in Israel. The last reported outbreak had occurred in 1981. From August to October 2000, a large-scale epidemic of WN fever occurred in Israel; 417 cases were confirmed, with 326 hospitalizations. The main clinical presentations were encephalitis (57.9%), febrile disease (24.4%), and meningitis (15.9%). Within the study group, 33 (14.1%) hospitalized patients died. Mortality was higher among patients >70 years (29.3%). On multivariate regressional analysis, independent predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(97 citation statements)
references
References 8 publications
4
92
1
Order By: Relevance
“…In 19 hospitalized patients in the New York epidemic, Weiss et al [11] found truncal rash in 3 patients (16%) and Asnis et al [5] in 2 out of 8 patients (25%), whereas Nash et al [3] reported a rash in 11 patients out of 59 (19%). In the 2000 West Nile fever outbreak in Israel [12], a macular rash was recorded in 51/233 (22%) of the hospitalized patients, but the study from Romania noted only 5% [13, 14]. When clinical data are available, the rash is described as a nonpruritic, ‘roseola-like’ or maculopapular rash on the chest, back and arms, which lasts 1 week [3, 5, 6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 19 hospitalized patients in the New York epidemic, Weiss et al [11] found truncal rash in 3 patients (16%) and Asnis et al [5] in 2 out of 8 patients (25%), whereas Nash et al [3] reported a rash in 11 patients out of 59 (19%). In the 2000 West Nile fever outbreak in Israel [12], a macular rash was recorded in 51/233 (22%) of the hospitalized patients, but the study from Romania noted only 5% [13, 14]. When clinical data are available, the rash is described as a nonpruritic, ‘roseola-like’ or maculopapular rash on the chest, back and arms, which lasts 1 week [3, 5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological complications include meningitis, encephalitis, meningoencephalitis, myelitis, cranial neuropathies, optic neuritis, ataxia or polyradiculitis [1,2,3,4,5,6]. Overall death rates for patients admitted to hospital during recent outbreaks ranged from 4 to 14% but were higher in older patients [1, 3, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s the clinical epidemiology of West Nile virus seems to have changed, with increasing frequency and severity of outbreaks, including urban disease (table). 24 13…”
Section: Historical Perspectivementioning
confidence: 99%
“…In recent outbreaks about two thirds of patients admitted to hospital had encephalitis (with or without signs of meningeal irritation), while one third had meningitis. 2 3 23 Severe generalised muscle weakness was common feature in the New York outbreak in 1999 and in subsequent outbreaks in the United States 23. In some patients this affects only the limbs, but in others respiratory and bulbar musculature are affected and patients require ventilation.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation